PENGARUH PERMAINAN TRADISIONAL TERHADAP PERKEMBANGAN GERAK MOTORIK ANAK PADA SISWA KELAS V SEKOLAH DASAR NEGERI CIPINANG I - Dedi Aryadi (Universitas Setia Budhi Rangkasbitung, 2018)
From all the results of the discussion above, it can be concluded that the traditional game for the development of motor movement in the fifth grade students of Cipinang Elementary School 1 District. Pandegalang, apparently has a significant influence. This is evidenced by the acquisition of the 40 meter run test, 10 meter change direction, and upright jump has a t-count value of 9.65, 11.99, and 4.66 which is outside the null hypothesis acceptance area with a value limit of 2.06 with a real level = 0.05 and degrees freedom = 0.25. So seeing these results, the traditional game is very influential to improve motor movement of fifth grade students of Cipinang Elementary School 1 District. Padeglang.